Northern Territory Criminal Trials 1873-1899 - Finnane, Mark (ADA Dataverse, 2019)
Northern Territory Supreme Court trials. During this period the court was in South Australian jurisdiction. This dataset was accessed by the Prosecution Project from data in historical newspapers (https://trove.nla.gov.au/)